El conocimiento de la persona en su singularidad. Una aproximación desde dos exponentes de la Escuela Tomista de Barcelona. - GARCÍA ELTON, Íñigo Alberto (Humanidades: Revista de la Universidad de Montevideo)
In this article we will present, in light of Jaime Bofill's and Francisco Canals' interpretation of the Duplex Cognitio thesis (expressed by Saint Thomas Aquinas in De Veritate X, 8), two modes of knowledge, one called "essential-objective" and the other "existential." Having done this, we will show that this last form of knowledge not only allows us to account for the knowledge that the soul has of itself through its own being, but also for the knowledge of another person in their singularity; thus showing that the other is present to those who know him in the manner of an immediate and dynamic presence, communicative of personal intimacy, and which we call "biography."